Company Size, Profitability, Tax, and Good Corporate Governance On The Company’s Decision To Transfer Pricing (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2015-2018 Period) - Arifin, Atwal; Saputra, Africo Al-Dua; Purbasari, Heppy (Universitas Muhammadiyah Surakarta, 2020)
The research is aimed to analyze the effect of company size, profitability, tax, and good corporate governance on the company’s decision to transfer pricing. The dependent variable in this study is transfer pricing which is proxied by the value of the related party transaction sale. The independent variables in this study are company size, profitability, tax, and KAP quality. This research used secondary data on financial reports or annual reports on manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2018 period. Determination of the sample employed purposive sampling method. The sample in this study were 22 companies with 88 data. The results in this study found that (1) company size had a positive effect on transfer pricing, (2) profitability had no effect on transfer pricing, (3) tax had no effect on transfer pricing, and (4) KAP quality had no effect on transfer pricing.